Development of a monoclonal antibody to study MARCH6, an E3 ligase that regulates proteins that control lipid homeostasis - Shimeng Xu; Linda Donnelly; Daniel L. Kober; Myra Mak; Arun Radhakrishnan (Journal of Lipid Research)
Membrane-associated ring-CH-type finger 6 (MARCH6), also designated as TEB4 or RNF176, is an E3 ligase that is embedded in membranes of the endoplasmic reticulum where it ubiquitinates many substrate proteins to consign them to proteasome-mediated degradation. In recent years, MARCH6 has been identified as a key regulator of several metabolic pathways, including cholesterol and lipid droplet homeostasis, protein quality control, ferroptosis, and tumorigenesis. Despite its importance, there are currently no specific antibodies to detect and monitor MARCH6 levels in cultured cells and animals. Here, we address this deficiency by generating a monoclonal antibody that specifically detects MARCH6 in cultured cells of insect, mouse, hamster, and human origin, as well as in mouse tissues, with minimal cross-reactivity against other proteins. We then used this antibody to assess two properties of MARCH6. First, analysis of mouse tissues with this antibody revealed that the liver contained the highest levels of March6. Second, analysis of five different cell lines with this antibody showed that endogenous levels of MARCH6 are unchanged as the cellular content of cholesterol is varied. This reagent promises to be a useful tool in interrogating additional signaling roles of MARCH6.